Aplikasi Geofisika Terpadu Untuk Penelitian Potensi Air Tanah Aquifer Batu Pasir di Alasombo, Indonesia - Fivry Wellda Maulana; Arie Noor Rakhman (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the potential of groundwater in Alasombo, Weru District, Sukoharjo Regency, Indonesia. The investigation has been carried out using geophysical methods that are integrated with surface geological data to obtain an interpretation of the hydrogeological control of the aquifer. The lithology of the aquifer is dominated by sandstone which controls its role as 2 types of aquifers, namely unconfined aquifers or free aquifers and semi-confined aquifers or semi-free aquifers. The geoelectrical section shows that the groundwater-carrying layer that functions as an aquifer is the sandstone layer in the second layer and sandstone in the base layer. As an artesian aquifer or a confined aquifer, sandstone aquifers have a water volume between 31.5 to 260 m3/day, in a northwest-southeast direction. In terms of the quality of the conductivity value of water in the field, below 1500 µs/cm is freshwater type groundwater that can be recommended as a source of clean water.